Construction of z-scheme Bi2WO6/SnS2 heterojunction photocatalyst for simultaneous rhodamine b degradation and Cr(VI) reduction under sunlight irradiation - Liaw, Si Jian (2023)

(untitled)
Industrial sewage often contain metal ions and dyes, which are difficult to be removed efficiently. Solar-light-driven heterogeneous semiconductor photocatalysis is recognized as a potential and efficacious approach for environmental remediation. Specifically, the heterojunction photocatalysts with low band-gaps and recombination rates are highly-valuable for this purpose. In this study, a novel Bi2WO6/SnS2 binary composite material was created via a hydrothermal-deposition method. Different analytical techniques were employed to investigate the photocatalyst’s physiochemical and optical properties. It discovered that the composite material had an extended visible light photosensitivity as a result of the reduced band gap of Bi2WO6/SnS2. The photocatalytic performance of Bi2WO6/SnS2 was assessed by using it to degrade RhB and reduce Cr(VI) under sunlight exposure for 180 minutes. Kinetic studies showed that Bi2WO6/SnS2-10 (10 wt% of SnS2) manifested the best performance, in which 95.5 % RhB (kapp = 0.0178 min-1 ) and 100 % Cr(VI) (kapp = 0.0513 min-1 ) removal efficiencies were achieved separately. Simultaneous removal of both pollutants further explored the ability of Bi2WO6/SnS2-10 to achieve the removal efficiency of 83.19 % for RhB (kapp = 0.0082 min-1 ) and 94.60 % for Cr(VI) (kapp = 0.0159 min-1 ). The phytotoxicity study also revealed that the toxicity of RhB-Cr(VI) mixed solution treated by Bi2WO6/SnS2-10 photocatalyst has been substantially reduced. This present work indicates the potential of Bi2WO6/SnS2 for use in photodegradation of organic pollutants and photoreduction of heavy metals.